The relationship between attachment, primary emotions and positive/negative spirituality: a path analysis - Anton Freund; Jürgen Fuchshuber; Jürgen Fuchshuber; Jürgen Fuchshuber; Giorgia Silani; Human-Friedrich Unterrainer; Human-Friedrich Unterrainer; Human-Friedrich Unterrainer; Human-Friedrich Unterrainer; Human-Friedrich Unterrainer (Frontiers Media S.A., 2024)
ObjectiveThe present study investigates what may influence individuals to experience their religiosity/spirituality as either subjectively positive [religious or spiritual (r/s) wellbeing] or as negative (r/s struggles). Drawing on existing literature attachment insecurity and the seven primary emotions as outlined by Jaak Panksepp in Affective Neuroscience are identified as likely influences.MethodsThe final sample consisted of 340 participants (age: M = 36, SD = 14.2; 68.5% = female), among which 65% self-identified as religious/spiritual. A path analysis was conducted to test a proposed mediation model in which the expected effects of primary emotions (B-ANPS) on r/s wellbeing (MI-RSWB) and r/s struggles (RSSS) were mediated through attachment insecurity (ECR-RD8).ResultsThe data indicated that attachment insecurity fully mediated the relationships between the primary emotions SADNESS and LUST with r/s struggles. Furthermore, the primary emotions FEAR and ANGER displayed small direct effects on both r/s struggles and r/s wellbeing. Overall, the model, which demonstrated excellent model fit, was able to explain 30% of the variance of r/s struggles, 24% of attachment insecurity and 5% of r/s wellbeing.ConclusionsThe findings suggest that primary emotions such as SADNESS and LUST substantially explain r/s struggles and that these relationships seem to be mediated through attachment. Moreover, r/s struggles seem to be qualitatively distinct from r/s wellbeing. Finally, a moderate link between LUST and attachment suggests that sexuality plays a significant role in (adult) attachment processes.